The effect of political Predicaments on the independence of the judiciary In Africa: the case of Zimbabwe (2000-2013) - Chapanduka, Doris (Midlands State University, 2017)
The purpose of this research is to scrutinize the impact of political crises on the judicial independence from 2000 to 2013. Zimbabwe experienced political crises that include violation of human rights, contested polls to mention just a few. These predicaments had a major and negative impact while only a few saw a shed of positivity on the bench. The study brings to light the lack of judicial independence and how this has negatively affected its constitutional mandated duties. The purpose of the judiciary is to act as a “vanguard” between the government and its people. Utilised in this research is documentary search, in-depth key and interviews that are nothing short of informative as data collection techniques. Brought to light would be the notion that separation of powers and rule of law are very crucial in assuring the independence of the judiciary which are a cornerstone to a democratic society. Failure of just and impartial execution of duties by the bench has been as a result of the erosion of the principle of separation of powers. This research suggests recommendations like the amendment or termination of POSA and AIPPA in an attempt to improve the status of judicial independence. Trusting the bench has become a thing of the past to most citizens of Zimbabwe and hence depoliticizing the criminal judicial system is just but a step further in regaining the trust of the masses. The judiciary needs to be out in full force and put its good efforts of exercising justice on the spotlight.